Treatment of Nevus Spilus with dual-wavelength copper vapor laser - Igor V. Ponomarev (State Scientific Center of Dermatovenereology and Cosmetology, 2021)
Introduction. Speckled lentiginous nevus or Nevus Spilus (NS) is a congenital or acquired melanocytic nevus. NS appears as dark hyperpigmented macules or papules interspersed in the lentigo-like hyperpigmentation patch. Surgical methods for removing NS, primarily on the skin with a thin dermis, are associated with the risk of disruption of its structure or scarring. The use of single wavelength laser irradiation allowed achieving pronounced bleaching of the NS area with such side effects as scars, post-inflammatory hyperpigmentation, and relapses in some cases. Side effects could occur due to the lack of complete blood flow in the microvascular bed near the NS. The study aimed to evaluate the efficacy of NS treatment with a dual-wavelength copper vapor laser (CVL).